Impact of pomelo peel pectin on chicken egg quality preservation - Nattha Jariyapamornkoon; Wimonwan Rotthung; Suchaya Pinyopornkasem; Wichai Sutthitham (Applied Food Research)
Pomelo peel pectin coating preserves egg quality by sealing eggshell pores, making it a useful alternative when refrigeration is unavailable. This research aimed to assess the effectiveness of pomelo peel pectin coating in maintaining the quality and nutritional content of chicken eggs during 35 days of storage at room temperature. The eggs were analyzed across four treatments: uncoated eggs stored at room temperature (URT, control), uncoated eggs stored at 4 °C (U4 °C), pomelo peel pectin coated eggs stored at room temperature (PRT), and pomelo peel pectin coated eggs stored at 4 °C (P4 °C). Weight loss percentage, Haugh unit (HU), yolk index (YI), and albumen pH were measured weekly. Nutritional composition (protein, fat, ash, moisture, carbohydrate, and energy) was determined every two weeks. Results showed that PRT had lower weight loss and higher HU and YI compared to URT. No significant differences were observed between U4 °C and P4 °C. Both refrigerated treatments retained a Grade A HU on day 35, whereas PRT maintained a Grade A HU until day 28. Pomelo peel pectin coating had no significant impact on albumen pH and nutritional values. Overall, the coating effectively preserved egg quality by reducing weight loss and maintaining HU and YI at room temperatures (25–30 °C). However, it did not show the same effects at 4 °C. Without refrigeration, the coating offers an alternative method for extending shelf life, maintaining Grade A HU for up to 28 days at room temperature.